Clinical practice guideline for the management of acute pancreatitis in the social security of Peru (Essalud) - Guzmán-Calderón, Edson (2023)
This article summarizes the clinical practice guideline (CPG) for the management of acute pancreatitis in the Social Security of Peru (EsSalud), to provide evidence-based clinical recommendations for the management of acute pancreatitis in EsSalud. A guideline development group (GEG) was formed that included medical specialists and methodologists. The GEG formulated 7 clinical questions to be answered by this CPG. Systematic searches of systematic reviews and -when considered relevant- primary studies were carried out in PubMed during 2022. The evidence was selected to answer each of the clinical questions posed. The certainty of the evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic work meetings, the GEG used the GRADE methodology to review the evidence and formulate the recommendations, the points of good clinical practice, and the corresponding flow charts. Finally, the CPG was approved with Resolution No. 105-IETSI-ESSALUD-2022. This CPG addressed 7 clinical questions on fluid therapy, start of enteral nutrition, analgesia, type of nutrition, antibiotic, and surgical treatment. Based on these questions, 8 recommendations (1 strong and 7 conditional), 13 BPCs, and 1 flowchart were formulated. Th odology and evidence-based conclusions of the CPG for the management of acute pancreatitis in EsSalud